Polytene chromosomes of Simulium (Psaroniocompsa) daltanhani (Diptera: Simuliidae) from Central Amazonia, Brazil - Hamada, Neusa; Da Silva Pereira, Eleny; Adler, Peter H. (Zootaxa, 2008)
Last-instar larvae of Simulium (Psaroniocompsa) daltanhani Hamada and Adler from a stream in Central Amazonia were analyzed cytologically by mapping their polytene chromosomes. Simulium daltanhani has the nucleolar organizer in the short arm of chromosome I, heterogametic females, and an absence of autosomal polymorphisms. The chromosomes carry multiple rearrangements relative to other analyzed members of the S. quadrifidum species group in the subgenus Psaroniocompsa. One-third of the chromosomal complement is rearranged relative to the sequence of S. ulyssesi, the species with the most similar banding pattern among studied members of the S. quadrifidum group.